2021
DOI: 10.1007/s11356-021-15992-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term exposure to fluorescent red polymer microspheres on Artemia franciscana nauplii and juveniles

Abstract: Microplastics (MPs) are ubiquitously present in the world’s seas with unknown potential toxic effects on aquatic ecosystems. The aim of this study was to evaluate biochemical responses caused by 1–5 μm diameter plastic fluorescent red polymer microspheres (FRM), under short-term exposure of nauplii and juveniles of Artemia franciscana, using a set of biomarkers involved in important physiological processes such as biotransformation, neuronal transmission and oxidative stress. Two FRM concentrations (0.4 and 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…These results agreed with previous studies that showed increased mortality (LC 50 40.95 mg L −1 ) of Artemia exposed to higher concentrations (1–100 μg mL −1 ) of PP-MPs 44 and PS-NPs (5–100 μg mL −1 ), 45 as well as PS-NH 2 (100 μg mL −1 ) 22 and PS-NH 2 (10 μg mL −1 ) for 48 h. 6 However, some studies reported no significant effects of MPs on the survival of different brine shrimp species. 23,27,46 This indicates that the size of M/NPs influences the ingestion, bioaccumulation, and survival of brine shrimp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agreed with previous studies that showed increased mortality (LC 50 40.95 mg L −1 ) of Artemia exposed to higher concentrations (1–100 μg mL −1 ) of PP-MPs 44 and PS-NPs (5–100 μg mL −1 ), 45 as well as PS-NH 2 (100 μg mL −1 ) 22 and PS-NH 2 (10 μg mL −1 ) for 48 h. 6 However, some studies reported no significant effects of MPs on the survival of different brine shrimp species. 23,27,46 This indicates that the size of M/NPs influences the ingestion, bioaccumulation, and survival of brine shrimp.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Among crustaceans Artemia, also known as brine shrimp has been widely used as an ecotoxicological model organism in the marine environment due to their short life cycles, and high fecundity. 23 These are small crustaceans inhabiting hypersaline waters, such as salt lakes, lagoons, and salt pans where they serve as a crucial food item for many fish larvae and play a key role in the energy transfer of the marine trophic chain. 24 NPs exposure leads to severe alterations in the development, morphology, and physiology of Artemia franciscana (A. franciscana), measured by various endpoints, such as oxidative stress, cell damage, biochemical and genetic modifications, and neurological and reproductive impairments 6,12,21,[25][26][27] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…PS- significantly reduced the ChE and CbE activities in A. franciscana at 1 mg/L [ 91 ]. Polymer spheres significantly increased the CbE and ChE activities in A. franciscana nauplii at 1.6 mg/L and significantly increased the CbE and ChE activities in A. franciscana juveniles at 0.4 and 1.6 mg/L [ 126 ]. For Cladocera, plain PS suspension increased the AChE activity, while the functionalized PS significantly decreased the AChE activity in D. magna [ 50 ].…”
Section: Effects Of Microplastics On Physiological Functions Of Aquat...mentioning
confidence: 99%
“…These offspring are considered ‘full clones’ with the same genotype and are genetically identical to their mother [18,19]. For Artemia , the subjects of biological research mainly focuses on diapause and de-diapause mechanism [20], viviparous and ovoviviparous reproduction regulation [21] and physiological response to the toxicological exposure [22,23].…”
Section: Introductionmentioning
confidence: 99%